Sukūk on blockchain: a legal, regulatory and Sharī’ah review - Adam Sa'ad, Auwal; Sherin, Kunhibava; Zakariyya, Mustapha; Aishath, Muneeza; Muhammad, Ershadul Karim (Emerald Publishing Limited, 2021)
Purpose – This paper aims to explore issues arising from sukūk (Islamic bonds) on blockchain, including Sharīʾah (Islamic law) and legal matters. Design/methodology/approach – A qualitative methodology is used in conducting this research where relevant literature on sukūk was reviewed. Through a doctrinal approach, the paper presents analyses on the practice of sukūk and sukūk on blockchain by discussing its legal, Sharīʾah and regulatory issues. This culminates in a conceptual analysis of blockchain sukūk and its peculiar challenges. Findings – This paper reveals that digitizing sukūk issuance through blockchain remedies certain inefficiencies associated with sukūk transactions. Indeed, structuring sukūk on a blockchain platform can increase transparency of underlying sukūk assets and cash flows in addition to reducing costs and the number of intermediaries in sukūk transactions. The paper likewise brings to light legal, regulatory, Sharīʾah and cyber risks associated with sukūk on blockchain that confront investors, practitioners and regulators. This calls for deeper collaboration in research among Sharīʾah scholars, lawyers, regulators and information technology experts. Research limitations/implications – As a pioneering subject, the paper notes the prospects of blockchain sukūk and the current dearth of literature on it. The paper would assist relevant Islamic capital market entities and authorities to determine the potential and impact of blockchain sukūk in their respective businesses and the financial system. Practical implications – Blockchain sukūk will assist in addressing issues inherent in classical sukūk and in paving the way to innovative solutions that will facilitate and enhance the quality of sukūk transactions. For that, sukūk would require appropriate regulatory technology to address its governance and regulation peculiarities. Originality/value – Integrating sukūk with blockchain technology will add value to it. The paper advances the idea that blockchain sukūk revolutionises sukūk and enhances its practice against known inadequacies.